2014
DOI: 10.1200/jco.2014.56.7156
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Surveillance and Success of Salvage Strategies After Definitive Chemoradiation in Patients With Esophageal Cancer

Abstract: Purpose Patients with esophageal carcinoma (EC) who are treated with definitive chemoradiotherapy (bimodality therapy [BMT]) experience frequent relapses. In a large cohort, we assessed the timing, frequency, and types of relapses during an aggressive surveillance program and the value of the salvage strategies. Patients and Methods Patients with EC (N = 276) who received BMT were analyzed. Patients who had surgery within 6 months of chemoradiotherapy were excluded to reduce bias. We focused on local relapse (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 17 publications
(13 reference statements)
0
67
0
Order By: Relevance
“…Of the patients who were candidates for salvage esophagectomy, their corresponding survival was quite good: median, 58.6 months; 3-year, 61%; and 5-year, 45%. An impressive 98% of the relapses developed within 3 years, indicating this is the period where regular surveillance is most important if the patient is considered a candidate for additional treatment (31).…”
Section: Risk Of Locoregional Vs Systemic Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Of the patients who were candidates for salvage esophagectomy, their corresponding survival was quite good: median, 58.6 months; 3-year, 61%; and 5-year, 45%. An impressive 98% of the relapses developed within 3 years, indicating this is the period where regular surveillance is most important if the patient is considered a candidate for additional treatment (31).…”
Section: Risk Of Locoregional Vs Systemic Recurrencementioning
confidence: 99%
“…Surveillance strategies differ nationally, with the primary variations found in the frequency of use for PET and endoscopy. To provide a basis for this discussion, an outline of a possible surveillance strategy is provided in Figure 3 that combines recommendations from the existing literature (3,31).…”
Section: Predicting the Risk Of Surveillancementioning
confidence: 99%
“…The decision between TMT and BMT is influenced by multiple factors, which have been discussed previously [9-11]. Although it has previously been shown that the locoregional relapse (LRR) rate is low after TMT [12-16], it is considerably higher after BMT [9, 10, 17]. We recently reported that only 2% of 518 patients treated with TMT benefited from surveillance/salvage strategies [12], bringing into question their usefulness in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Salvage surgery after definitive CRT is appropriate and has good outcomes in responding patients. 74,75 A series of data on nonrandomized patients from the FFCD 9102 trial suggest that attempting surgery after early failure of CRT is beneficial and should be considered in patients who are still operable. 76 A retrospective propensity score-matched study included 65 patients with esophageal AC who underwent salvage esophagectomy after failed definitive CRT and compared this group to 65 matched patients who received planned esophagectomy.…”
Section: The Role Of Salvage Surgery After Crtmentioning
confidence: 99%